Pop-up book of bajakah plant (Spatholobus littoralis) inventory results as learning media on biodiversity concept: A feasibility analysis - Alevin Wahyudi; Anisyah Yuniarti; Syamswisna Syamswisna (Department of Biology Education, Universitas Pendidikan Indonesia, 2023)
This research aims to analyze the feasibility of a pop-up book regarding the results of an inventory of Bajakah plants as a learning medium on biodiversity concepts. This research is descriptive. The research instrument used was the pop-up book media validation sheet, consisting of three aspects: consistency, format, and attractiveness. The pop-up book media was validated by five validators consisting of two Biology Education lecturers and three Biology teachers for 10th grade of senior high school. Data analysis was performed using Content Validity Ratio (CVR) analysis and Content Validity Index (CVI) analysis. The pop-up book media validation analysis results obtained a CVR of 0,99 and a CVI of 0,99. The value obtained is classified as valid so that the pop-up book can be declared feasible as a learning medium. This pop-up book can be used in learning biodiversity concepts for 10th grade of senior high school.